Cross-Domain Priming From Mathematics to Relative-Clause Attachment: A Visual-World Study in French - Pozniak, Céline; Hemforth, Barbara; Scheepers, Christoph (Frontiers in Psychology, 2018)
Human language processing must rely on a certain degree of abstraction, as we can produce and understand sentences that we have never produced or heard before. One way to establish syntactic abstraction is by investigating structural priming. Structural priming has been shown to be effective within a cognitive domain, in the present case, the linguistic domain. But does priming also work across different domains? In line with previous experiments, we investigated cross-domain structural priming from mathematical expressions to linguistic structures with respect to relative clause attachment in French (e.g la fille du professeur qui habitait à Paris / the daughter of the teacher who lived in Paris). Testing priming in French is particularly interesting because it will extend earlier results established for English to a language where the baseline for relative clause attachment preferences is different form English: in English, relative clauses (RCs) tend to be attached to the local noun phrase (low attachment) while in French there is a preference for high attachment of relative clauses to the noun phrase (NP). Moreover, in contrast to earlier studies, we applied an online-technique (visual world eye-tracking). Our results confirm cross-domain priming from mathematics to linguistic structures in French. Most interestingly, we found that in mathematically skilled participants, the effect emerged very early on (at the beginning of the relative clause in the sound stream) and is also present later (at the end of the relative clause), whereas in less mathematically adept participants, the effect was weaker. In line with previous findings, our experiment suggests that mathematics and language share aspects of syntactic structure at a very high level of abstraction.